Human resources development through training - Garcia, Ramon M. (1977)
The recognition of the importance of developing human capital has brought about Human Resources Development (HRD) which traces its beginnings to personnel training. HRD consists of planned and expertly designed courses geared to the training and development needs of a target clientele. It requires the support of activities such as: manpower forecasting and planning-, human resource accounting, and personnel records management. Its success is measured by the participants' positive application of what has been learned and the increased efficiency in the delivery of services to their respective beneficiaries.
Keywords: Personnel management; Public administration -- Management; Human Resource Development (HRD)